Critical Success Factors And Their Impact On The quality security decisions.: An analytical exploratory study of the opinions of a sample of leaders in the Iraqi Ministry of Interior) - Hurajah Alhasnawi, Hussein; Mosa Mahmoud, Gasan (Iraqi Journal for Administrative Sciences, 2024)
The research aims to demonstrate the impact of critical success factors (goals and strategy, organizational culture, senior management support, information technology infrastructure, organizational infrastructure, and human resource management) on the quality of security decisions (perception, rational measures, procedural justice, adherence to the decision) of a sample of Leadership in the Ministry of Interior (the Ministry of Administration and Financial Affairs Agency), as the size of the surveyed sample reached (180) individuals, and the questionnaire was the main tool for data collection, and a number of statistical methods such as confirmatory factor analysis and the correlation coefficient (Pearson) were used to measure the type and degree of relationship between the variables. Research and Structural Equation Modeling (SEM) to measure influence relationships, and the research reached a set of conclusions, the most important of which is the existence of a correlation and positive influence for critical success factors in the quality of security decisions. The research also came out with some recommendations, the most important of which is directing attention by the competent authorities on the topic of critical success factors Because it is one of the issues that directly affect the quality of security decisions, whether in normal or extraordinary circumstances.